Collaborative Study of Thresholds for Mutagens: Hormetic Responses in Cell Proliferation Tests Using Human and Murine Lymphoid Cells - Shizuyo Sutou; Akiko Koeda; Kana Komatsu; Toshiyuki Shiragiku; Hiroshi Seki; Toshiyuki Kudo (SAGE Publishing, 2021)
Background: We previously showed that hormetic responses can be established in cell activity tests using human and murine adherent cells. This time, we examined whether hormetic responses can be established in cell proliferation tests using suspended human and murine lymphoid cells. Methods: Human lymphoblastoid cells (TK6) and mouse lymphoma cells (L5178Y) were cultured in multi-well culture plates and treated with mitomycin C, ethyl methansulfonate, hygromycin B, aclarubicin or colchicine at various dose levels and the number of cells was measured at varied times using a flow cytometer. Results: When the ratio of the number of cells treated with a test chemical to those in the negative control was plotted, the dose-response relationship typically showed a reverse U-shaped curve, indicating the occurrence of hormesis and existence of thresholds in cell toxicity. The hormetic responses depended largely on the test chemical, dose level and exposure time. When examining responses over the course of time, a J-shaped or fallen S-shaped curve was also observed. Conclusions: The dose-response relationship showed a reverse U-shaped curve, a hallmark of hormesis, at least some time points for all chemicals tested here, indicating that chemical hormesis can be established in in vitro cell proliferation tests.